INVESTIGATING INDONESIA’S ENERGY TRADE EFFICIENCY: GRAVITY AND MALMQUIST INDEX APPROACH - Desti Candrasari; Putu Mahardika Adi Saputra (Department of Economics, Faculty of Economics and Business, Universitas Brawijaya, 2017)
This paper applies Gravity and Malmquist index approach to investigate energy trade efficiency between Indonesia and East Asia Countries (i.e. Japan, South Korea, and China). Gravity model is employed to identify the inputs that will be used in computing the energy trade efficiency; meanwhile, Malmquist index approach to identify the energy trade efficiency by taking data from 2000-2015. One of the findings shows that the considered inputs that will be utilised are population of importer countries, Indonesian population, relative distance, and ratio of added value of industry sector towards GDP. In addition, the energy trade efficiency between Indonesia and East Asia countries from 2000 to 2015 was composed by technical change or technical/ potential change. China averagely had the highest efficiency and showed improvement like South Korea did. Japan showed, on the other hand, deterioration.